Influence of grazing activities on species diversity of dung beetles in Mediterranean pastures - Numa C.; Rueda R.; Verdú J.R.; Galante E. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
We evaluated whether different types of grasslands lead to different patterns of dung beetle assemblages by comparing two different management conditions of grasslands in central Spain. Four different sites of grasslands with high wild herbivory (deer, roe deer) were sampled inside of Cabañeros National Park and four sites with traditional agrosilvipastoral management were sampled in a sheep farm in the nearby of the park. Dung beetle species richness didn't vary among grassland conditions but total dung beetle abundance and biomass were considerably greater in park grasslands than in the grasslands of the sheep farm. Despite of the high similarity among the sampled sites in both hydric content and availability of dung, dung beetle species composition and abundance from both park and farm sites were different. These results suggest that management activities like ploughing affecting soil structure and the use of veterinary substances affecting dung quality could be important factors affecting dung beetle assemblages in terms of composition, abundance and biomass in Mediterranean ecosystems.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)